Degradation of bending properties of flax fiber reinforced polymer after natural aging and accelerated aging. (20th April 2020) - Wang, Xiaomeng; Petrů, Michal
Highlights: The bending properties of FFRP under natural aging conditions are measured. The relationship between natural aging and accelerated aging is studied. The residual mechanical property model may be applied in life prediction of FFRP. Abstract: In this paper, the effect of natural aging and accelerated aging on the bending properties of flax fiber reinforced polymer (FFRP) is studied. Test results show that the flexural strength decreases by 11.2%, 14.9%, 15.5%, and the flexural modulus decreases by 21.3%, 32.3%, 35.8%, after 60 days, 120 days and 180 days of natural aging, respectively. Then accelerated test is carried out to predict the long-term performance of FFRP. The results show that short-term exposure test (just considering the temperature and humidity) cannot achieve the same effect on mechanical property degradation as natural aging. A modified residual mechanical property model of FFRP is established according to the test results.